Association of proton pump inhibitor use with the risk of the development or progression of albuminuria among Japanese patients with diabetes: A prospective cohort study [Diabetes Distress and Care Registry at Tenri (DDCRT 16)]. (April 2018) - Hayashino, Yasuaki; Okamura, Shintaro; Mashitani, Tsuyoshi; Tsujii, Satoru; Ishii, Hitoshi; ,
Highlights: It is not unclear if proton pump inhibitor (PPI) use is associated with subsequent risk of impaired renal function or the development or progression of albuminuria in patients with diabetes. PPI use is not associated with the subsequent risk of estimated glomerular filtration rate decline. PPI use is not also associated with the development nor progression of albuminuria in patients with diabetes. Abstract: Aims: We aimed to determine the prospective association between proton pump inhibitor (PPI) use and the subsequent risk of the development or progression of albuminuria or eGFR. Methods: Longitudinal data of patients with diabetes were obtained from a large Japanese diabetes registry. To assess the independent correlation between PPI use and the development or progression of urine microalbuminuria, the time-varying Cox proportional hazards model was used with adjustment for potential confounders. Results: The mean patient age, body-mass index (BMI), and hemoglobin A1c (HbA1c) levels were 65.7 y, 24.5 kg/m 2, and 7.5% (57.9 mmol/mol), respectively. In 1711 patients without albuminuria, we observed 599 cases with development of albuminuria over median follow-up of 4.0 years, and in 1279 patients with microalbuminuria, 290 cases with urinary albuminuria progression over 4.0 years, and 257 eGFR decline cases over 3.8 years. PPI use was not associated with the development of albuminuria (HR = 0.88; 95%CI, 0.77–1.01; p = .058), progression of albuminuria (HR = 1.24; 95%CI, 0.87–1.79; p = .236), nor eGFR decline (HR = 1.05; 95%CI, 0.81–1.34; p = .973) even in a propensity score-adjusted model with time-varyingly updating PPI use information. Conclusions: In conclusion, PPI use was not associated with the subsequent risk of development or progression of albuminuria, or eGFR decline in patients with diabetes.